THE USE OF SKIMMING STRATEGI TO IMPROVE STUDENTS’ READING COMPREHENSION : A STUDY AT UNIVERSITY OF TIMOR - Sefrina Maria Seuk Asa; Noer Jihad Saleh; H. Sudarmin Harun (Jurnal Sahabat Keperawatan, 2019)
The objectives of the research were to find out if there was any significant improvement of students’ comprehension in reading through skimming technique.the use of this research is pre-experiment design, based one group pre-test and post-test. The subjects of this research were the second semester students at University of Timor. The result of research showed that score mean post-test is higher of the pre-test. The score mean pre-test is 39.38 up to post-test is 73.50 it means that, after treatment the students has the higher score mean post-test. The result t-test of the students pre-test and pos-test is 13.68, than the result standar deviation of pre-test is 16.79 and than post-test of standar deviation is 11.82. there was a statistically significant improvement of students’ reading comprehension. This suggests that the skimming technique can facilitate the students to improve their reading comprehension.